2016
DOI: 10.3390/ijms17060955
|View full text |Cite
|
Sign up to set email alerts
|

Enriched Astaxanthin Extract from Haematococcus pluvialis Augments Growth Factor Secretions to Increase Cell Proliferation and Induces MMP1 Degradation to Enhance Collagen Production in Human Dermal Fibroblasts

Abstract: Among many antioxidants that are used for the repairing of oxidative stress induced skin damages, we identified the enriched astaxanthin extract (EAE) from Haematococcus pluvialis as a viable ingredient. EAE was extracted from the red microalgae through supercritical fluid carbon dioxide extraction. To compare the effectiveness, EAE wastreated on human dermal fibroblasts with other components, phorbol 12-myristate 13-acetate (PMA), and doxycycline. With sirius red staining and quantitative real-time polymerase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 27 publications
3
60
0
2
Order By: Relevance
“…Matrix metalloproteinases are enzymes activated by UV exposure or inflammation. They contribute to the breakdown of collagen while inhibiting new collagen formation . We confirmed that the upregulation of TIMP‐1 might contribute to the declining of MMP‐1 and ‐3 expressions..…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Matrix metalloproteinases are enzymes activated by UV exposure or inflammation. They contribute to the breakdown of collagen while inhibiting new collagen formation . We confirmed that the upregulation of TIMP‐1 might contribute to the declining of MMP‐1 and ‐3 expressions..…”
Section: Discussionsupporting
confidence: 74%
“…Nevertheless, during times of environmental stress, such as ultraviolet B (UVB) or heat exposure, the ROS level increases strongly, resulting in considerable damage to cellular functions and structures. In the current studies it was demonstrated that the accumulation of ROS decreased organism salubrity because the oxidative damage was a contributor to the senescence . Aging is a natural process for everyone, evoking various diseases, and skin is highly responsive to photo‐aging due to oxidative stress created by ROS .…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…Antioxidative compounds derived from natural plant species may help keep human skin at a physiologically healthy state by decreasing oxidative stress [1]. By reducing oxidative stress from reactive oxygen species (ROS), antioxidative compounds can prevent ROS-induced skin damage [2].…”
Section: Introductionmentioning
confidence: 99%